Penerapan Asesmen Kompetensi Minimum (AKM) Terhadap Motivasi Dalam Pembelajaran Pada Mapel PAI - Asy’ari, M. (Khazanah : Journal of Islamic Studies, 2023)
The minimum competency assessment is an assessment of the basic competencies required by all basic students who are able to develop their own capacities and participate positively in society. There are two fundamental competencies measured by AKM, namely reading literacy and numeracy. This research aims to determine the improvement in student learning outcomes by using AKM. The form of research uses a riched library approach, whuch uses the literature study method. The results of this research are that minimum competency assessment can also be used as a reference for the PAI map in its application of calculating competence. Literacy competency represents cognitive abilities that are oriented toward High order thinking skills (HOTS) characteristhic of AKM which are based on CBT and use more varied types of Questions applied to the application of PAI. Seen from the aim of AKM, namely improving the quality of education through assessment to develop student’s abilities and character at school, motivation and intereset in learning students in each subject which is needed to support student learning achievement as well s behavior in daily life.